Epigallocatechin-3-Gallate Plus Omega-3 Restores the Mitochondrial Complex I and F0F1-ATP Synthase Activities in PBMCs of Young Children with Down Syndrome: A Pilot Study of Safety and Efficacy - Iris Scala; Daniela Valenti; Valentina Scotto D'Aniello; Maria Marino; Maria Pia Riccio; Carmela Bravaccio; Rosa Anna Vacca; Pietro Strisciuglio (MDPI AG, 2021)
Down syndrome (DS) is a major genetic cause of intellectual disability. DS pathogenesis has not been fully elucidated, and no specific pharmacological therapy is available. DYRK1A overexpression, oxidative stress and mitochondrial dysfunction were described in trisomy 21. Epigallocatechin-3-gallate (EGCG) is a multimodal nutraceutical with antioxidant properties. EGCG inhibits DYRK1A overexpression and corrects DS mitochondrial dysfunction in vitro. The present study explores safety profiles in DS children aged 1-8 years treated with EGCG (10 mg/kg/die, suspended in omega-3, per os, in fasting conditions, for 6 months) and EGCG efficacy in restoring mitochondrial complex I and F0F1-ATP synthase (complex V) deficiency, assessed on PBMCs. The Griffiths Mental Developmental Scales-Extended Revised (GMDS-ER) was used for developmental profiling. Results show that decaffeinated EGCG (>90%) plus omega-3 is safe in DS children and effective in reverting the deficit of mitochondrial complex I and V activities. Decline of plasma folates was observed in 21% of EGCG-treated patients and should be carefully monitored. GMDS-ER scores did not show differences between the treated group compared to the DS control group. In conclusion, EGCG plus omega-3 can be safely administered under medical supervision in DS children aged 1-8 years to normalize mitochondria respiratory chain complex activities, while results on the improvement of developmental performance are still inconclusive.